Composition characterization and transformation mechanism of refractory dissolved organic matter from an ANAMMOX reactor fed with mature landfill leachate. (February 2018) - Li, Zhang; Kechen, Xu; Yongzhen, Peng
Graphical abstract: Highlights: Stable NRR and ORR of 5.95 kg N/m 3 /day and 0.77 kg DOC/m 3 /day were achieved. EEM-PARAFAC model is an efficient way to identify the species and content of rDOM during ANAMMOX process. A novel metabolism mechanism of rDOM in ANAMMOX reactor was established. Anaerolineaceae is possible primary degraders for rDOM. Abstract: This study applied combined spectroscopy techniques to assess rDOM compositional characteristic and investigated its transformation mechanisms during the treatment of mature landfill leachate by ANAMMOX process. A novel rDOM metabolism mechanism was proposed in this study for the first time. A stable, high nitrogen removal rate of 5.95 kg N/m 3 /day and a rDOM conversion efficiency of 51% were achieved in ANAMMOX reactor (AR). In additionally, the initial rDOM removal was closely related to sludge adsorption, with the adsorption force mainly originating from electrostatic interaction and hydrophobicity. As the operating time increased, the removal mechanism of rDOM in the AR changed from adsorption to adsorption-biodegradation and finally stabilized. Furthermore, Anaerolineaceae, associated with the hydrophobic reaction, were the primary degraders for the rDOM and Candidatus Kuenenia dominated the nitrogen consumption. rDOM removal efficiency was suggested to be increased by a moderate enhancement of Anaerolineaceae content in the AR.